A pH/redox-dual responsive, nanoemulsion-embedded hydrogel for efficient oral delivery and controlled intestinal release of magnesium ions. Issue 7 (3rd February 2021) - Huang, Yu; Wang, Zewei; Zhang, Guiju; Ren, Jie; Yu, Li; Liu, Xuhan; Yang, Yuanxi; Ravindran, Abirami; Wong, Chloe; Chen, Rongjun
Abstract : A pH/redox-dual responsive, nanoemulsion-embedded composite hydrogel was proposed to well retain magnesium ions in the highly acidic gastric environment, but efficiently release them in the neutral and reducing intestinal environment. Abstract : It remains a major challenge to achieve efficient oral delivery and controlled intestinal release of ions using hydrogels. Herein, we report a novel, pH/redox-dual responsive, nanoemulsion-embedded composite hydrogel to address this issue. The hydrogel was first synthesized by crosslinking a biocompatible, pH-responsive pseudopeptide, poly(l -lysine isophthalamide) (PLP), and redox-sensitive l -cystine dimethyl ester dihydrochloride (CDE). A suitable amount of magnesium acetate was encapsulated into oil-in-water nanoemulsions, which were then embedded into the lysine-based hydrogel. The resulting composite hydrogel collapsed into a compact structure at acidic gastric pH, but became highly swollen or degraded in the neutral and reducing intestinal environment. The ion release profiles indicated that the nanoemulsion-embedded composite hydrogel could well retain and protect magnesium ions in the simulated gastric fluid (SGF) buffer at pH 1.2, but efficiently release them in the simulated intestinal fluid (SIF) buffer at pH 6.8 in the presence of 1, 4-dithiothreitol (DTT) as a reducing agent. Moreover, this composite hydrogel system displayed good biocompatibility. These results suggested that the pH/redox-dual responsive, nanoemulsion-embedded composite hydrogel could be a promising candidate for efficient oral delivery and controlled intestinal release of magnesium and other ions.